Multifunctional Chiral Three-Dimensional Phosphite Frameworks Showing Dielectric Anomaly and High Proton Conductivity - Yu, S. S.; Xu, C. Y.; Pan, X.; Pan, X. Q.; Duan, H. B.; Zhang, H. (Frontiers in Chemistry, 2021)
A chair 3D Co(II) phosphite frameworks have been prepared by ionothermal method. It belongs to chiral space group P3221 and the whole framework can be topologically represented as a chiral 4-connected qtz net. It shows multi-step dielectric response arising from the reorientation of the Me2-DABCO in the chiral cavities. It also can be served as pron conductor with high conductivity, 1.71 × 10-3 S•cm-1, at room temperature, which is attributed to the formation of denser hydrogen-bonding networks providing efficient proton-transfer pathways.